(untitled) (Fiep Bulletin - online, 2014)
The present study aimed to investigate the social representations that the students of Physical Education UNIGRANRIO have on teacher formation, for it adopted the Theory of Social Representations (MOSCOVICI, 1978), as a research tool that is able to understand and intervene in reality. The research objective was to present results of a study that is being developed in the Laboratory of the Research Group on Social Representations in/ for Teacher Formation - LAGERES-Unigranrio, it seeks to identify the possible elements that guide representations of undergraduates. We adopted the methodology of mixed type (NOVIKOFF, 2010), it was used Curtograma test and free recall of words, the procedures were through interviews. The results indicate that students associate the representation of "teacher training" to the institution, whenever questioned the "work" is ahead of "study" in all cases, although students. The study reached the conclusion that for students, the institution is responsible for the training of teachers and in most cases the study is placed second, in relation to work.